Pictorial Campaigns on Intimate Partner Violence Focusing on Victimized Men: A Systematic Content Analysis - Reis, Eduardo; Arriaga, Patrícia; Moleiro, Carla; Hospital, Xavier (Frontiers in Psychology, 2020)
Men who are victimized in their intimate different-sex and same-sex relationships often report not having information to help them escape their abusive situations. To overcome this lack of information, public awareness campaigns have been created. But thus far, there isn’t a clear understanding of how these campaigns reflect theoretical principles central to improve message effectiveness and avoid undesired negative effects. This study aims to review the content of Intimate Partner Violence (IPV) pictorial campaigns focusing on victimized men in different and same-sex relationships. Specifically, it aims to understand the campaigns’ global characteristics, and if their content represents constructs from different theoretical models. Online search engines were used to extract pictorial campaigns in English, Spanish and Portuguese, released up until 2019. They must have had to be promoted by a formal organization, and were coded according to a theoretically grounded taxonomy, using thematic analysis. Our results indicate that out of the 57 campaigns collected, most were aimed at men without specifying the relationship they were in (i.e. different-sex or same-sex) (n=22, 39%), and intended to change attitudes, beliefs and behaviors about IPV (in line with the Theory of Planned Behavior) (n=47, 82%). Additionally, four campaigns adequately integrated fear appeal constructs of the Extended Parallel Processing Model (n=4, 7%), while 41 campaigns highlighted dissonant states in line with the Elaboration Likelihood Model (n=41, 72%). Following the Transtheoretical Model, most campaigns targeted victims in the Maintenance stage (n=52, 92%). The campaigns under analysis may prove useful for some victimized men, mostly presenting messages designed to elicit beneficial attitude and behavior change. Our analysis highlights different limitations as well, such as the lack of information on susceptibility to IPV (n=13, 23%) and the effectiveness of the recommended responses the campaigns provide (n=20, 38%), which may interfere with adequate fear appeal processing. Additionally, presenting more diverse victims may be beneficial, along with social norms change information regarding gender roles, violence and help-seeking. This may guide the development of improved and tailored campaigns to better facilitate help-seeking in victimized men that mostly avoid undesired negative effects on the viewer.